The Concept of Wahdat al-Wujud Ibn 'Arabi's Thought and its Relevance in Sufism - Yogi Fery Hidayat (Yayasan Adra Karima Hubbi, 2024)
This study examines the concept of Wahdat al-Wujud in Ibn 'Arabi's thought and its relevance to modern Sufism. Wahdat al-Wujud is a metaphysical view that asserts that the entire universe is merely a manifestation of the singular and absolute existence of God. The research employs a qualitative method with a literature review approach to analyze Ibn 'Arabi's thought through his major works such as Futuhat al-Makkiyah and Fushush al-Hikam, and to explore criticisms of this concept, particularly from figures such as Ibn Taymiyyah. The findings indicate that Wahdat al-Wujud has not only had a significant impact on the development of classical Sufism but also remains relevant in modern Sufi practices, especially in spiritual practices that emphasize human unity and awareness of God. Despite theological criticisms, particularly concerning accusations of pantheism, Wahdat al-Wujud continues to be a foundational principle in many mystical practices and understandings within Islam. This study offers a new perspective on the application of Wahdat al-Wujud in contemporary spiritual life and its contribution to modern understandings of Sufism.